U.S. multinationals and cash holdings - Gu, Tiantian (Journal of Financial Economics, 2017)
U.S. multinational firms hold significantly more cash than domestic firms. I study this cash differential using a dynamic model featuring corporate physical and intangible investment, cross-border decisions, and financial policies. I find that the cash differential diminishes by 42% if repatriation costs are set to zero. Hence, costly repatriation induces cash accumulation offshore. Further, firms that invest overseas have different ex ante cash policies from firms that do not. I examine this self-selection effect by eliminating heterogeneous intangibility across multinational and domestic firms, which reduces the cash differential by 28%. I also examine the likelihood of corporate inversion under federal regulations. The estimated annual tax loss to the U.S. Treasury from inversions is reduced from 2.2 billion to 1.3 billion if the requirements for foreign ownership are tightened from 20% to 50%.